ANALISIS KEBUTUHAN SISTEM PENJUALAN BARANG BERBASIS WEB - Fadhli Ranuharja (Jurnal Teknologi Informasi dan Pendidikan, 2018)
The purpose of this research is to design an information system web-based services which selling goods for College academic community in Padang City. Sales service information system is a whole system of activities indicated for planning, pricing, promoting and distributing goods, services, ideas to the target market in order to achieve organizational goals. Information systems generate marketting services website services for the sale of goods academic community in Padang City. Information system design services is the sale of goods, carried out by using the programming language Java Enterprise Edition (JEE) and a MySQL database. To provide security (security) to the data and information, then use the session